ISOLASI DAN PENETAPAN KADAR ALKALOID EKSTRAK ETANOLIK BUNGA KEMBANG SEPATU (Hibiscus rosa-sinensis L.) SECARA SPEKTRODENSITOMETRI - Mimiek Murrukmihadi; Kurniati Pamungkas (Majalah Obat Tradisional, 2015)
This research aims to isolate and determine relative concentration of alkaloid in Hibiscus rosa-sinensis L flowers. using spectrodensitometry. Ethanolic extract of H. rosa-sinensis flowers was made by maceration methode using etanol 70% as solvent. Fractionation of alkaloid compound was using VLC (Vaccum Liquid Chromatography) and using organic solfent mixture of methanol-ethyl acetate in variation concentration. Isolate was used as standard curve, then the concentration of H. rosa-sinensis flowers extract was determined using spectrodensitometry with silica gel as stationer phase and ethyl acetate: methanol ( 1:5 v / v) as mobile phase. The relative concentration of alkaloid was calculated by using standard curve Y = 29023.75 X + 5809.35, r = 0.996. Determination of isolate showed the relative concentration of alkaloid was 0.210 ± 0.035 % and this can be used as marker compound.